(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: To see the common indications, pattern of complications (during and post operative) of emergency tracheostomy in the tertiary level hospital in Bangladesh. It also gives the idea for minimizing the complications. Methods: This cross sectional study was carried out in the Department of Otolaryngology & Head- Neck surgery of Dhaka Medical College Hospital, Dhaka, from 14th April 2015 to 14th October 2015. This study includes all emergency patients irrespective of age and sex whose tracheostomy was done in emergency operation theatre of ENT department of Dhaka Medical College and Hospital. Results: The study reveals that the commonest indications of emergency tracheostomy were diagnosed case of carcinoma of larynx & base of tongue (30%) followed by post-irradiated carcinoma larynx (24%). Next common indications were stridor in undiagnosed case (18%), difficulty in intubation during surgery (10%), history of road traffic accident (6%), cut throat injury (6%), foreign body in throat (2%), laryngeal edema and blunt trauma in neck (2%) respectively. Commonest complications during the procedure were apnoea (12%), haemorrhage (18%), injury to surrounding structure (10%), cardiac arrest (4%) & respiratory arrest (2%). Common complications in early post operative period were surgical emphysema (10%), crusting or blockage (4%), tube dislodgement (4%), &stomal infection (2%). Late post operative complications were stomal granulation tissue (4%), pneumonia (2%), stomal infection (2%), tracheocutaneous fistula (2%), & tracheomalasia (2%). Bangladesh J Otorhinolaryngol; October 2016; 22(2): 96-101